The lattice of ordinable topologies (2013)
We demonstrate that the ordinable topologies for a set X areprecisely those that occupy the upper part of the lattice of topologies for X, and that they determine a lattice, not always complete or distributive. We also found the amount of complements, and principal complements, for certainordinable topologies, generalizing a known result of P. S. Schnare.